Dementia risk factors for Australian baby boomers - Peter K. Panegyres; Victoria Gray (MDPI AG, 2010)
Baby boomers are individuals born in the years 1946 to 1965. The objective of this paper was to define the risk factors for dementia and Alzheimer's disease (AD) and their relevance to Australian baby boomers, with the aim of providing evidence-based guidelines for dementia prevention. A series of PubMed searches (1994-2010) were conducted with relevant key words. Data was included from the Australian Bureau of Statistics (ABS) in relation to baby boomers in Australia. Article titles and abstracts were assessed by two reviewers for inclusion. Searches through ABS revealed no specific study on baby boomers at a national level; information was only available for Western Australia, South Australia and Queensland. A number of genetic and non-genetic risk factors for dementia were identified most of which remain controversial and require further study. We did not identify significant differences in the prevalence and incidence of dementia in those under 65 years in Queensland, South Australia and Western Australia. There were no correlations of risk factors and dementia between the Australian states. Modification of risk factors has not been proven to reduce the incidence and prevalence of dementia and AD in baby boomers. Nevertheless, on available evidence, we recommend: i) active management of cardiovascular risk factors such as hypertension; ii) the encouragement of a healthy lifestyle (eg, weight reduction, exercise) as offering the best pathways to reduce the emerging dementia risk for baby boomers. The implications are that activities promoting a healthy heart might lead to a healthy brain and help to prevent dementia.